Dermoscopy and In Vivo Confocal Microscopy Findings of Basal Cell Carcinomas in Xeroderma Pigmentosum Patients - Nilay Duman; Göktürk Oraloğlu; Banu Yaman; Işıl Karaarslan (Wolters Kluwer Medknow Publications, 2024)
Background: Xeroderma pigmentosum (XP) is a rare inherited disorder with a high incidence of malignant tumours. Literature data on dermoscopic and in vivo reflectance confocal microscopy (RCM) findings in patients with XP are very limited. Methods: Dermoscopic findings in 32 biopsy-proven BCCs and RCM findings in 10 biopsy-proven BCCs developed in seven XP patients were reviewed. Results: Of 32 BCCs, 28 were pigmented. On dermoscopy, BCCs exhibited multiple grey-blue globules/dots (81, 3%), short-fine telangiectasias/fine arborising vessels (65, 6%), multiple grey-blue ovoid nests (53, 1%), white structures (white-red structureless areas/shiny white areas/lines/strands) (56, 3%), arborising vessels (37, 5%), brown nests/globules/dots (28, 1%), spoke-wheel structures (9, 4%), leaf-like areas (9, 4%), ulceration (28, 1%), peripheral network (21, 9%), and multiple aggregated yellow-white globules (3, 1%). In 10 lesions in which further imaging with RCM was performed, RCM findings differentiated BCC from other tumours, including primary melanoma. Conclusions: Although the dominancy of pigmented structures may imitate melanoma clinically, dermoscopy is a valuable tool in the early diagnosis of BCCs in patients with XP. For suspicious lesions, RCM can help in differentiating pigmented BCC from primary melanoma.